Pengembangan Profesionalisme Guru Di Bekasi Untuk Menciptakan Iklim Emosional Kelas - Diamah, Aodah; Rahmawati, Yuli; Fitri, Susi; Rahmadianty, Anna; Mawarni, Pramita Cucu (Universitas Negeri Surabaya, 2023)
The community service workshop aimed to develop the teachers' professionalism in creating a positive classroom emotional climate. Teachers need to take effective action to improve the quality of structured learning which can be done by improving their professionalism in influencing a positive classroom climate. 48 teachers from SMA Tambun Bekasi participated in this community service workshop. The methodology used in the research included presentations, informative discussion, demonstration, exercise, and practice which were carried out through four main stages. The four main stages were introduction, implementation, guidance, and evaluation. This study used the Classroom Emotional Climate (CEC) instrument. The CEC instrument consists of nine dimensions, namely caring, control, clarity, challenge, motivation, consolidation, collaboration, learning attitudes, and behavioral emotion regulation. After participating in the workshop, the teachers were able to implement what they have learned from the workshop to improve the positive emotional classroom climate of their classroom. Moreover, they have also conducted an evaluation using the CEC instrument taught in the workshop.